Segmental reversal of the small bowel as an alternative to intestinal transplantation in patients with short bowel syndrome. - Panis, Y (1997)
OBJECTIVE: This article reports the results of segmental reversal of the small bowel on parenteral nutrition dependency in patients with very short bowel syndrome. SUMMARY BACKGROUND DATA: Segmental reversal of the small bowel could be seen as an acceptable alternative to intestinal transplantation in patients with very short bowel syndrome deemed to be dependent on home parenteral nutrition. METHODS: Eight patients with short bowel syndrome underwent, at the time of intestinal continuity restoration, a segmental reversal of the distal (n = 7) or proximal (n = 1) small bowel. The median length of the remnant small bowel was 40 cm (range, 25 to 70 cm), including a median length of reversed segment of 12 cm (range, 8 to 15 cm). Five patients presented with jejunotransverse anastomosis, and one each with jejunorectal, jejuno left colonic, or jejunocaecal anastomosis with left colostomy. RESULTS: There were no postoperative deaths. Three patients were reoperated early for wound dehiscence, acute cholecystitis, and sepsis of unknown origin. Three patients experienced transient intestinal obstruction, which was treated conservatively. Median follow-up was 35 months (range, 2 to 108 months). One patient died of pulmonary embolism 7 months postoperatively. By the end of follow-up, three patients were on 100% oral nutrition, one had fluid and electrolyte infusions only, and, in the four other patients, parenteral nutrition regimen was reduced to four (range of 3 to 5) cyclic nocturnal infusions per week. Parenteral nutrition cessation was obtained in 3 of 5 patients at 1 years and in 3 of 3 patients at 4 years. CONCLUSION: Segmental reversal of the small bowel could be proposed as an alternative to intestinal transplantation in patients with short bowel syndrome before the possible occurrence of parenteral nutrition-related complications, because weaning for parenteral nutrition (four patients) or reduction of the frequency of infusions (four patients) was observed in the current study.